K.H. Abdul Wahid Hasyim: DEMOKRATISASI MAZHABIYAH HINGGA REKONSILIASI POLITIK - Bakir, Bakir (JURNAL AT-TURAS, 2016)
The mazhabiyah (school of thought differentiation) issue is conceived as the ultimate problem of Muslims, since a life without mazhab, without ideological point, will be chosen as a the central determinant of social unity. For Abdul Wahid Hasyim, the madzhabiyah is important due to its function as a way of mutual understanding and peace building. He made it as a religious stance in the battle for maintaining the nation unity in diversity. This study attempts to portray religious and political contribution of Abdul Wahid Hasyim in upholding the Indonesian Islam and contructing NKRI. His contribution during Dutch colonialism, Japanese occupation, until independence periods had figured out his spirit as santri in the nation building.